Does Innovativeness Matter? Moderating The Link Between Intention And Digital Zakat Payment In Indonesia - Sari, Dia Purnama; Qoyum, Abdul; Hanafi, Syafiq Mahmadah (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2025)
Purpose: Despite advancements in digital infrastructure, the adoption of digital zakat platforms among Indonesian muzakki remains uneven. This study aims to investigate the determinants influencing muzakki’s intention and behavior in adopting digital zakat payment platforms by extending the UTAUT model through the integration of electronic trust (e-trust) and personal innovativeness in technology (PIT), offering a context-specific perspective within Islamic philanthropy.Design/methodology: This study employed a quantitative approach. An online questionnaire was distributed using purposive sampling to Indonesian Muslims with experience or awareness of digital zakat platforms. A total of 338 muzakki were collected from 32 Indonesian provinces. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed model and hypotheses.Findings: The findings indicate that performance expectancy and social influence have a significant and positive impact on the intention to pay zakat digitally. Furthermore, intention significantly predicts actual usage behaviour, with this relationship being positively moderated by personal innovativeness in technology. However, effort expectancy, facilitating conditions and e-trust are found to have no significant effect on intention.Practical Implication: The study offers practical insights for zakat institutions (e.g. BAZNAS and LAZNAS), platform developers and policymakers. Promoting digital literacy, engaging religious leaders ansocial influencers and designing inclusive, user-friendly platforms are essential to enhance participation. Cultivating individual openness to technology is also critical for sustaining digital zakat behaviour. Although e-trust was not found to significantly influence intention, maintaining platform transparency, credibility and reliability remains crucial for fostering long-term user confidence and acceptance.Originality/Value: This study contributes to Islamic marketing and digital philanthropy literature by extending the UTAUT model by incorporating e-trust and PIT in the context of digital zakat. he findings provide a novel perspective on technology acceptance in faith-based financial ecosystems, particularly in Muslim-majority countries undergoing rapid digital transformation